Analisis Pengelolaan Arsip Dinamis di PT ABC - Windi Lestari; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
Archives are a collection of documents, recordings, or important information that is systematically compiled, stored, and managed for reference, documentation, or records of the past. Archives are used to maintain records of organizations or individuals over a certain period of time. Archives can be divided into several types based on various criteria, including dynamic archives. Dynamic archives are a category of documents or records that continue to undergo changes, updates, or additions over time. This includes documents that are still active and used in the daily operations of an organization or business entity. Dynamic archives refer to a category of documents or records that undergo frequent changes, updates, or additions. Examples of dynamic archives include ongoing correspondence, projects in progress, or monthly financial records. It is important to maintain and manage dynamic archives well, ensuring easy access to necessary information while it is still in active use while maintaining data order and security. Along with time, some documents in a dynamic archive may become static or historical archives when the information is no longer needed in daily operational activities and is moved to long-term storage.